Religious Revitalization among the Kiowas : the Ghost Dance, Peyote, and Christianity - Kracht, Benjamin R., 1955- (University of Nebraska Press, 2018)
"Framed by theories of syncretism and revitalization, "Religious Revitalization among the Kiowas" examines changes in Kiowa belief and ritual in the final decades of the nineteenth century"--